Bcl-2 regulation of the inositol 1,4,5-trisphosphate receptor and calcium signaling in normal and malignant lymphocytes: Potential new target for cancer treatment - Greenberg, Edward F. (2014)
The anti-apoptotic protein Bcl-2 is a versatile regulator of cell survival. Its interactions with its own pro-apoptotic family members are widely recognized for their role in promoting the survival of cancer cells. These interactions are thus being targeted for cancer treatment. Less widely recognized is the interaction of Bcl-2 with the inositol 1,4,5-trisphosphate receptor (InsP(3)R), an InsP(3)-gated Ca(2+) channel located on the endoplasmic reticulum. The nature of this interaction, the mechanism by which it controls Ca(2+) release from the ER, its role in T-cell development and survival, and the possibility of targeting it as a novel cancer treatment strategy are summarized in this review.